2001
DOI: 10.1046/j.1529-8027.2001.01008-2.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant Axonal Neuropathy Locus Refinement To A < 590 KB Critical Interval

Abstract: Giant axonal neuropathy (GAN) is a rare autosomal recessive neurodegenerative disorder, characterised clinically by the development of chronic distal polyneuropathy during childhood, mental retardation, kinky or curly hair, skeletal abnormalities and, ultrastructurally, by axons in the central and peripheral nervous systems distended by masses of tightly woven neurofilaments. We recently localised the CAN locus in 16q24.1 to a 5‐cM interval between the D16S507 and D16S511 markers by homozygosity mapping in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Linkage of families 9, 14, and 15 to the GAN locus was previously demonstrated by homozygosity mapping Cavalier et al, 2000). Genetic studies of family 16 with polymorphic markers LC8, LC6, D16S3098, GAAT2CO8 and D16S505 demonstrated linkage to 16p24.1 with a LOD score of 3.1 at θ = 0 ( Fig.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Linkage of families 9, 14, and 15 to the GAN locus was previously demonstrated by homozygosity mapping Cavalier et al, 2000). Genetic studies of family 16 with polymorphic markers LC8, LC6, D16S3098, GAAT2CO8 and D16S505 demonstrated linkage to 16p24.1 with a LOD score of 3.1 at θ = 0 ( Fig.…”
Section: Resultsmentioning
confidence: 58%
“…Numbering of families 9, 14, and 15 is according to Bomont et al (2000). The patients from these three families were shown to be homozygous for all 16q24.1 markers tested (12, 5 and 4 markers respectively; Cavalier et al, 2000;Bomont et al, 2000). Although the parents of family 15 are not consanguineous, they originate from the same mountainous village.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A central role for E3-ligase activity in the turnover of NF was discovered through studies of GAN (Bomont et al, 2000), a fatal autosomal recessive neuropathy (Cavalier et al, 2000) in which giant axons (up to 50 μm in diameter) filled with densely packed and disorganized NF are found throughout the peripheral and central nervous system (Asbury et al, 1972). Starting early in infancy, the disease is associated with progressive loss of motor and sensory function (Johnson-Kerner et al, 2014).…”
Section: Degradation and Turnover Of Nfmentioning
confidence: 99%